1996
DOI: 10.1128/aac.40.11.2545
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intramacrophage activity of resorcinomycin A against Mycobacterium avium-Mycobacterium intracellulare complex after liposome encapsulation

Abstract: The activities of free and liposomal resorcinomycin A against Mycobacterium avium-Mycobacterium intracellulare complex (MAC) grown in broth and in murine peritoneal macrophages were evaluated. Liposomal resorcinomycin A was composed of dimyristoyl phosphatidylcholine and phosphatidylinositol at a molar ratio of 9:1. Both free resorcinomycin A and liposomal resorcinomycin A showed no toxicity to macrophages at concentrations up to 50 micrograms/ml, as determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The -Flores et al, 1996;Onyeji et al, 1994aOnyeji et al, , 1994bOnyeji et al, 1995). Additionally, Faria and…”
Section: Nps Delivery and Intracellular Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…The -Flores et al, 1996;Onyeji et al, 1994aOnyeji et al, , 1994bOnyeji et al, 1995). Additionally, Faria and…”
Section: Nps Delivery and Intracellular Uptakementioning
confidence: 99%
“…The NPs have an advantage of releasing persistently and tardily in the intracellular targeted location. The process of biodegradable NPs-drugs in the intracellular is dynamic and complicated, including intracellular trafficking, endocytosis, releasing, and -Flores et al, 1996;Onyeji et al, 1994aOnyeji et al, , 1994bOnyeji et al, 1995). Additionally, Faria and Roman reported that the PLGA loading isoniazid analog could increase the drug concentrations located inside of the macrophages to kill the Mycobacterium tuberculosis (de Faria et al, 2012).…”
Section: Nps Delivery and Intracellular Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Examples include, but are not limited to, novel drug delivery systems, as is the case of nebulized liposomes for pulmonary targeting [ 26 , 42 , 43 , 48 , 66 , 67 , 68 , 69 ], nano-formulations and polymeric particles [ 64 , 70 , 71 ], and chemical compounds restoring antimicrobial susceptibility, among which efflux pump inhibitors deserve to be mentioned [ 72 , 73 ].…”
Section: Static Intracellular Infection Modelsmentioning
confidence: 99%
“…Monocytes, macrophages Gentamicin 1990 [79] Monocyte-derived macrophages Streptomycin 1992 [80] Murine J 774 cells Azithromycin, rifabutin, clarithromycin 1994 [81] Rifampicin 2009 [82] Human blood-derived macrophages Sparfloxacin 1996 [83] Human macrophages Ciprofloxacin and azithromycin 1995 [84] Ofloxacin; clarithromycin 1994 [48] Murine peritoneal macrophages Granulocyte-macrophage colony-stimulating factor Resorcinomycin 1995 [85] 1996 [86] Mycobacterium bovis Alveolar macrophages Rifampicin Liposomes 2009 [87] Mycobacterium tuberculosis…”
Section: Staphylococcus Aureusmentioning
confidence: 99%